Living Tafsir in Ponorogo Pesantren: Epistemic Typologies of Female Ulama on Gendered Scriptural Readings - Muyassaroh, Iffah Khoiriyatul; Siregar, Maragustam; Marhumah, Marhumah (UIN Sunan Kudus, 2025)
This study examines the living tafsir among female ulama in pesantren in Ponorogo and how they construct meaning from scriptural texts often considered gender-biased through the ethical framework of Maqāṣid al-Sharī‘ah (objectives of Islamic law) and the methodology of mubādalah (mutuality). Using an Interpretative Phenomenological Analysis (IPA) approach, data were collected through in-depth interviews, participant observation in Qur’anic study sessions, and analysis of instructional tafsir (interpretation) materials. The findings identify two main typologies: an ethical, conservative orientation that maintains textual fidelity while emphasizing relational moral reasoning to protect dignity, family, and social harmony; and a dialogical, transformational orientation that interprets texts contextually to affirm justice, shared responsibility, and women’s participation in the public sphere without neglecting ethical decorum. The study shows that interpretive authority emerges not solely from textual mastery but from lived religious experience enacted repeatedly through pedagogical practice and social relations. Conceptually, the study positions living tafsir as a legitimate epistemic category in contemporary Qur’anic studies, with implications for Islamic education that promote moral sensitivity, critical reflection, and relational justice.